2012
DOI: 10.1055/s-0032-1316350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Moderate Physical Training on the Leptin Synthesis by Adipose Tissue of Adult Rats Submitted to a Perinatal Low-protein Diet

Abstract: The aim of the study was to verify if moderate physical training affects leptin content in visceral and subcutaneous adipose tissue of adult rats subjected to a low-protein diet during the perinatal period. Male Wistar rats were divided into 2 groups according to their mother's diet during gestation and lactation: control (17% casein, C, n=12) and low-protein (8% casein, LP, n=12). On postnatal day 60, half of each group was submitted to moderate physical training (8 wks, 5 d · wk - 1, 60 min · d - 1, at 70% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Adult exercise was also beneficial in IUGR rats induced by severe maternal nutrient restriction in gestation, where voluntary exercise (1 hour/day from 60 to 250 days of age, 56 m/day) reduced body fat percentage at 100, 150, and 250 days and body weight at 250 days compared with IUGR sedentary controls (74). Consistent with the lower adipose leptin expression after exercise training reported in the low-protein-induced IUGR rat (26), 190 days of voluntary wheel running tended (nonsignificantly) to diminish the elevated levels of serum leptin in IUGR rats from severely maternally nutrient-restricted pregnancies compared with their IUGR sedentary controls (74). In that study of severe maternal global nutrient restriction, exercise also significantly reduced the plasma concentrations of free fatty acids, glycerol, and triglycerides in control and IUGR progeny, although only plasma triglycerides were elevated in IUGR without exercise (74).…”
Section: Insulin Sensitivitysupporting
confidence: 64%
See 2 more Smart Citations
“…Adult exercise was also beneficial in IUGR rats induced by severe maternal nutrient restriction in gestation, where voluntary exercise (1 hour/day from 60 to 250 days of age, 56 m/day) reduced body fat percentage at 100, 150, and 250 days and body weight at 250 days compared with IUGR sedentary controls (74). Consistent with the lower adipose leptin expression after exercise training reported in the low-protein-induced IUGR rat (26), 190 days of voluntary wheel running tended (nonsignificantly) to diminish the elevated levels of serum leptin in IUGR rats from severely maternally nutrient-restricted pregnancies compared with their IUGR sedentary controls (74). In that study of severe maternal global nutrient restriction, exercise also significantly reduced the plasma concentrations of free fatty acids, glycerol, and triglycerides in control and IUGR progeny, although only plasma triglycerides were elevated in IUGR without exercise (74).…”
Section: Insulin Sensitivitysupporting
confidence: 64%
“…In these relatively young rats, a moderate exercise training regimen (8 weeks, 5 day/week, 60 min/day, up to 18.3 m/min) from 60 to 120 days of age normalized the accelerated postnatal growth and reduced lean mass in IUGR rats and normalized the elevated leptin content of adipose tissue in IUGR rats at 120 days of age compared with sedentary IUGR animals (26). Adult exercise was also beneficial in IUGR rats induced by severe maternal nutrient restriction in gestation, where voluntary exercise (1 hour/day from 60 to 250 days of age, 56 m/day) reduced body fat percentage at 100, 150, and 250 days and body weight at 250 days compared with IUGR sedentary controls (74).…”
Section: Insulin Sensitivitymentioning
confidence: 90%
See 1 more Smart Citation
“…However, exposure to a low-protein diet (8 % casein) during gestation followed by the consumption of a normoproteic diet throughout the life course was associated with catch-up growth, but when maternal protein restriction is continued during lactation, there is long-lasting growth restriction even when the offspring are recovered [37]. Supported by previous studies, moderate physical training recovered the body weight of low-protein offspring by a mechanism that probably includes an increase in lean mass [38,39].…”
Section: Discussionmentioning
confidence: 88%
“…The underlying mechanism may include the normalization of some hormone concentrations such as leptin, IGF-1, and glucocorticoids that were programmed by perinatal malnutrition [44,45]. Previous studies have shown that regular moderate physical training attenuated the effects of perinatal low-protein diet on the secretion of leptin by visceral adipose tissue, the phenotype of skeletal muscle fiber, and the morphology of the spleen in adult offspring submitted to perinatal low-protein diet [13,38,39].…”
Section: Discussionmentioning
confidence: 99%